Alexandre Jacob, forçat anarchiste en Guyane : politique ou droit commun ? - Colombe de Dieuleveult (Criminocorpus)
The issue of political offences and crimes, different from the common law offences, is characterized by its intricacy, not so much in terms of special treatment in the execution of the sentence but firstly, in terms of the legal definition of political offence. In this regard, the case of the anarchists at the end of the XIXth century is particularly interesting : fundamentally political, their actions were sentenced under the common law system, hardened by the so-called “villainous laws” (lois scélérates) that turned anarchism into an aggravating circumstance. The writings of Alexandre Jacob, anarchist convict in French Guyana, shed light on the specific status of transported anarchist convict as well as they show the evolution of a political commitment and thought.